KURIKULUM HUMANISTIK DAN PENDIDIKAN KARAKTER: SEBUAH GAGASAN PENGEMBANGAN KURIKULUM MASA DEPAN - Dwi Setiyadi (Universitas PGRI Madiun, 2011)
Humanistic curriculum gives rise to the coverage of need of self-actualization of the students so as to develop and to build integrity. The social reconstructionists suggests that social needs are available in any individual interest. The obligation of a curriculum is to generate the better future through a social reformation. Social values and their application should be accommodated in critical thinking process framed by a curriculum; in the way that curriculum has become the best vehicle for the students to develop their skill in grasping with the learning materials, understanding the personal and local problems. Personality, social values, thinking skill, problem solving skill can be all developed altogether through a curriculum – which in return can bring about the better future of human nature.